UPACARA MANE’E PADA MASYARAKAT KAKOROTAN KECAMATAN NANUSA KABUPATEN KEPULAUAN TALAUD - Laira, Merlin (Universitas Sam Ratulangi, 2016)
The background of this study was to determine and describe one of the cultural heritage of traditional fishing carried out in the village Kakorotan Sub Nanusa district Talaud islands known as the ceremony mane'e, mane'e tradition in society Kakorotan a unique culture and a social event that contains the values for the benefit of society. This study aims to provide information relating to the implementation of the traditional ceremony mane'e ranging from initial preparation to the summit ceremony as well as the benefits the ceremony on people's lives, this study using a qualitative descriptive study to describe the cultural, social groups in the ceremony mane'e. Sources of data obtained from the village government, traditional leaders, religious leaders, and local communities as well as through photographs and video footage of traditional ceremonies mane'e implementation, data were collected through observation, interviews and documentation study. This study concluded that the implementation mane'e ceremony begins with a period of abstinence or e'ha for 1 year both on land and at sea, about three months before the ceremony village leaders, indigenous, religious ceremonies to invoke the protection of a brief thanksgiving to the Creator in order to be given the smoothness, safety, and the results at the time of the ceremony. After that the measures will be implemented is marra'ca pundangi, mangolom par'ra, mattuda tampa pane'can, mamabi'u sam'mi, mamotto'u sam'mi, manganu ina, ina,, matahia manar'maalama This research can be used as a reference for the community and the government in preserving regional cultures, especially the traditional ceremony in public Kakorotan Talaud Islands. Keywords: ceremony, mane'e, e'ha.